2021
DOI: 10.1007/s11356-021-14611-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential of organic and inorganic amendments for stabilizing nickel in acidic soil, and improving the nutritional quality of spinach

Abstract: Contamination of soils by nickel (Ni) has become a serious environmental problem throughout the world, and this substance wields dangerous effects on the ecosystem and food chain. A pot experiment was conducted to examine the effect of rice straw (RS), rice straw biochar (BI) and calcite (CC) at 1% and 2% application rates in a Ni contaminated soil. The objective was to potentially stabilize Ni and reduce its bioavailability to spinach (Spinacia Oleracea L.). Spinach plants were grown in a Ni contaminated Ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Some phytochemicals have an antioxidative action, for example, carotenoids, flavonoids, and other phenolics [13]. Previous studies have shown that spinach grown in soil treated with organic amendments showed higher leaf quality due to an increase in nutrients, antioxidant enzymes, photosynthetic pigments, and bioactive compounds (polyphenols, flavonoids, and carotenoids) [14][15][16][17]; this is due to the changes that organic amendments cause in the properties and structure of the soil [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some phytochemicals have an antioxidative action, for example, carotenoids, flavonoids, and other phenolics [13]. Previous studies have shown that spinach grown in soil treated with organic amendments showed higher leaf quality due to an increase in nutrients, antioxidant enzymes, photosynthetic pigments, and bioactive compounds (polyphenols, flavonoids, and carotenoids) [14][15][16][17]; this is due to the changes that organic amendments cause in the properties and structure of the soil [17].…”
Section: Introductionmentioning
confidence: 99%